Penggunaan Plasma Darah Untuk Bahan Obat Dalam Perspektif Hukum Islam - Sayyidah Mafisah; Oman Fathurohman sw (STIKes Ibnu Sina Ajibarang, 2024)
The use of blood plasma as a medicinal ingredient is a matter of debate among scholars and medical experts. In Islam, blood is considered unclean and is prohibited from being used for decorative purposes. So, it is necessary to carry out a legal analysis regarding using blood plasma as a medicinal ingredient from an Islamic perspective. This research discusses the law of using blood plasma as a medicinal ingredient from an Islamic perspective. The research method uses a qualitative descriptive method with a literature study approach. The data sources used were Islamic literature, ulama fatwas, and scientific research on the use of blood plasma. The research results show that blood plasma as a medicinal ingredient in Islam is permitted if it is used for medicinal purposes and to improve the quality of life. if used for decoration, it is haram. This conclusion is based on Islamic principles which permit the use of unclean items for medicinal purposes to maintain survival. MUI Fatwa No. 45/2018 concerning the Use of Blood Plasma for Medicinal Ingredients determines that blood plasma is sacred because of its properties (smell, taste, and color). The use of blood plasma as a medicinal ingredient in Islam is permitted if it is used for medicinal purposes and to improve quality of life